2004
DOI: 10.1177/0886260504263871
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Symptoms and Life Skill Needs of Domestic Violence Victims

Abstract: This study identified the trauma symptoms and life skill needs of 84 domestic violence victims from three domestic violence programs. Women completed two self-report tools: Trauma Symptom Inventory (TSI) and Occupational Self Assessment (OSA). Staff members participated in focus groups regarding their perceptions of the women's needs. Women scored within the clinical range on the Defensive Avoidance (39.8%), Intrusive Experiences (30.1%), and Tension Reduction Behavior (24.1%) clinical scales of the TSI. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 24 publications
3
51
0
Order By: Relevance
“…Disengagement also relates to social withdrawal that was found to increase PTSD; increased engagement was predictive of more positive mental health (Taft, Resick, Panuzio, Vogt, & Mechanic, 2007). Finally, one's perception of poor coping ability was linked to increased trauma symptoms (Gorde, Helfrich, & Finlayson, 2004). No effects of education, marital status.…”
Section: Individual Risk Factors A) Copingmentioning
confidence: 97%
“…Disengagement also relates to social withdrawal that was found to increase PTSD; increased engagement was predictive of more positive mental health (Taft, Resick, Panuzio, Vogt, & Mechanic, 2007). Finally, one's perception of poor coping ability was linked to increased trauma symptoms (Gorde, Helfrich, & Finlayson, 2004). No effects of education, marital status.…”
Section: Individual Risk Factors A) Copingmentioning
confidence: 97%
“…Mental illness and homelessness create a cycle of functional impairment that results in an inability to achieve and retain the basic skills necessary for living independently. Functional impairments impact an individual's personal health, functioning, productivity in personal and vocational areas, and his/her ability to maintain social relationships (Goodman et al 1991;Gorde et al 2004;Sullivan et al 2000). Individuals with mental illness often have difficulty maintaining stable housing and functioning independently in the community and may welcome support for daily activities such as budgeting, shopping, and cleaning, which improve their ability to manage their lives independently (Calysn et al 2002;Schutt and Goldfinger 1996).…”
Section: Overviewmentioning
confidence: 99%
“…IPV is also linked to poor employment stability, and a high use of welfare (Busch & Wolfer, 2002;Kimmerling et al, 2009). Researchers found that both victims of IPV and emergency shelter staff members considered that increasing abused women's IADL skills, (such as seeking and retaining employment, parenting, budgeting, time management, social navigation skills to locate community resources for housing, child care services and employment services) were the most urgent intervention priority (Gorde, Helfrich, & Finlayson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A scientific review of interventions for violence against women revealed that no studies have evaluated the usefulness of screening to reduce violence or improve women's health, nor were there any studies evaluating the success rate of shelter stay as a means to decrease incidences of violence . While a systematic review (Helfrich & Rivera, 2006) revealed advocacy, career counseling plus conscious awareness, cognitive behavioral counseling, cognitive trauma therapy, peer support groups, and safety planning as being beneficial for female victims of IPV, little information is available as to the efficacy and relevance of life skills interventions for this population (Gorde et al, 2004;Helfrich & Rivera, 2006).…”
Section: Introductionmentioning
confidence: 99%